2016
DOI: 10.1515/jiip-2015-0090
|View full text |Cite
|
Sign up to set email alerts
|

Use of difference-based methods to explore statistical and mathematical model discrepancy in inverse problems

Abstract: Normalized differences of several adjacent observations, referred to as pseudo-measurement errors in this paper, are used in so-called difference-based estimation methods as building blocks for the variance estimate of measurement errors. Numerical results demonstrate that pseudo-measurement errors can be used to serve the role of measurement errors. Based on this information, we propose the use of pseudo-measurement errors to determine an appropriate statistical model and then to subsequently investigate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…We note that a misspecified statistical error model can lead to an incorrect estimation of the parameters as well as their uncertainly bounds. With the assumption on the errors E j (i.e., i.i.d, mean zero, and constant variance) in the previous section, there are generally two ways of selecting the correct statistical error model, namely, using residual plots or applying second-order differencing techniques directly to the data [4,5]. We briefly discuss these methods below.…”
Section: Methods For Selection Of a Statistical Error Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that a misspecified statistical error model can lead to an incorrect estimation of the parameters as well as their uncertainly bounds. With the assumption on the errors E j (i.e., i.i.d, mean zero, and constant variance) in the previous section, there are generally two ways of selecting the correct statistical error model, namely, using residual plots or applying second-order differencing techniques directly to the data [4,5]. We briefly discuss these methods below.…”
Section: Methods For Selection Of a Statistical Error Modelmentioning
confidence: 99%
“…In addition, if the correct mathe- matical model is not used, residual plots could give inaccurate information, as these plots also depend on the solution of the mathematical model as well as on the chosen γ value. A method that relies only on the data itself for identifying the correct observational statistical error model is a second-order differencing technique and is described in detail in [4]. This method is found to be more accurate and efficient than using residual plots [4] as well as not requiring prior solution of inverse problems.…”
Section: Second-order Differencing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial treatment of the inverse problem in [2] suggested that the ATN model cannot capture some aspects of aphid population dynamics. Therefore, we first use difference-based pseudo-measurement errors, as described in [7], to test our statistical model without tacitly assuming a mathematical model. We compute estimates of the measurement error, f γ (t j ;θ)ǫ j , from the observed N j 1 .…”
Section: Formulation Of the Inverse Problemmentioning
confidence: 99%
“…We assume an error model in the form of (8), but a more generalized form of error model for GLS methods can be found in [3,4,14,16,32]. GLS estimatesθ θ θ n and estimated weights {ω j (θ θ θ)} n j=1 are found using a standard iterative method [2,4,14,16,32] as given below .…”
Section: Residual Plots and Generalized Least Squaresmentioning
confidence: 99%